Perception analysis of climate change and adaptations by smallholder farmers in Nepal - Ghimire, NP; Aryal, M; Regmi, PP; Thapa, RB; Pande, KR; Pant, KP (Journal of Agriculture and Environment, 2018)
Climate change is posturing warning on present and future food security in low income countries. But, the actual effect of the climate change is still unknown. This study examined the farmer’s perception on climate change and strategies employed to adapt using primary and secondary data collected through household survey and reported by government. Statistical analysis is used for exploring the adaptations by farmers for the negative impact of climate change on domestic production of major cereals crops. The results are discussed at district level empirically and major variables are found statistically significant. This study conclude that there is a need for adaptations strategy by government authority in environmental management and agricultural sustainability in Nepal to come to terms with negative impacts of climate change and likely positive and beneficial response strategies to global warming. The paper suggests some policy measures for improving adaptations and food security situation in the country and open up some areas for further research.